Tevrat Usupovych Gorgiladze: a brilliant surgeon who contributed to further advances in the Filatov’s method of penetrating keratoplasty (Ukrainian Journal of Ophthalmology, 2024)
The present article reports on the life and scientific and clinical activities of Prof. Tevrat Usupovych Gorgiladze and his contributions to further advances in the Filatov’s method of partial penetrating keratoplasty (PPK). T.U. Gorgiladze, a Filatov’s pupil and a brilliant surgeon, was heading the Corneal Transplantation Department for 20 years. During this period, he elucidated various problems in, and proposed many techniques for the diagnosis and treatment of anterior segment pathology. The Corneal Transplantation Department was the first department established by Acad. Filatov at the institute that now bears his name.